Respon Pemberian Mikoriza Arbuskular Dalam Media Zeolit Terhadap Pertumbuhan Dan Hasil Tanaman Kedelai - Usnawiyah Usnawiyah; Khaidir Khaidir (Faculty of Agriculture, Universitas Malikussaleh, 2019)
Arbuscular mycorrhiza expected to increase the growth and yield of soybean. However, during the application requires another materials as growth media or spores carrier such as compos and zeolite. Zeolites are used as promoters for plant growth and development for the better through the efficient use of fertilizers. These minerals can retain nitrogen content in the soil, improve the quality of solid organic fertilizer and liquid waste. Zeolites can improve the efficiency of fertilizer use, both in stimulating plant growth and development and to increase agricultural output. Furthermore, it will support the work function of arbuscular mycorrhiza as root simbion